Optical Waveguide Refractive Index Sensor for Biochemical Sensing - Cheng Peng; Changjin Yang; Huan Zhao; Lei Liang; Chuantao Zheng; Chen Chen; Li Qin; Hui Tang (Applied Sciences, 2023)
This study describes the basic principles of optical waveguide refractive index sensing and the various design structures of refractive index sensors. These waveguides generate different optical resonances, which cause changes in the sensing refractive index and temperature and are subsequently used to detect the concentration in the analyses. First, the structural characteristics and performance indices of the microring sensor and interferometer are studied based on the refractive index of the optical waveguide. Second, the principle and sensing detection mechanism of the two types of refractive index sensing employed in these sensors are analyzed. Then, the two sensors are classified and discussed from the perspective of the waveguide materials and structures, as well as the substances to be measured. Simultaneously, performance indicators such as sensitivity and detection range are compared and summarized. The comparison results show that there is a compromise between the sensitivity and quality factor of the optical waveguide refractive index sensor. Finally, applications of refractive index sensing in the biochemical field for material detection are discussed, showing that the optical waveguide refractive index sensor has significant advantages over other types of biochemical optical sensors.